Designs and optimizations of active and semi-active non-linear suspension systems for a terrain vehicle - Lajqi, Shpetim (Strojniški vestnik, 2012)
This paper introduces a design and optimization procedure for active and semi-active non-linear suspension systems regarding terrain vehicles. The objective of this approach is the ability to quickly analyze vehicles' suspension performances resulting from passive, active, or semi-active systems. The vehicle is represented by a mathematical model regarding a quarter of it, and equations for motion are derived and solved by using MATLAB/Simulink. In order to verify the reliability of the derived computer program, a comparison is made with one of the comprehensive commercial software packages. The decision parameters of the active damping device are optimized by using the Hooke-Jeeves method, which is based on non-linear programming. The usefulness of the treated active and semi-active systems on a concrete terrain vehicle is presented and compared with the presented passive systems by analyzing the vehicle's body acceleration, velocity, displacement, and vertical tire force, namely those aspects that directly influence driving comfort and safety.
Keywords: aktivne obese; optimizacija obes; pasivne obese; polaktivne obese; terenska vozila